Otosclerosis: presentation,diagnosis and management - Mazhar, Khadija; Chaudhry, Sadia; Masood, Sundas; Rehman, Abdur (Journal of Rawalpindi Medical College, 2026)
Hearing loss profoundly affects quality of life, limiting communication, social interaction, and occupational performance. It is also associated with emotional distress, social isolation, and an increased risk of cognitive decline when left untreated. This case report describes a young male presenting to the ENT OPD with progressive hearing loss in bilateral ear. After exclusion of all associated symptoms and previous history, etiology was sought via otoscopy, revealing a perfectly mobile and normal-looking tympanic membrane. PTA and tympanometry revealed bilateral carhart notch and A-type curve on tympanometry, respectively, making the diagnosis of clinical otosclerosis. Patient underwent exploratory tympanotomy and Stapedotomy with a prosthesis. Follow-up PTA showed closure of air bone gap. Otosclerosis, though benign, is twice as common in females than male. This case illustrates the classical presentation of otosclerosis in a male patient and highlights the role of keen history taking and high clinical suspicion in a male patient where otosclerosis is often missed as a differential diagnosis of progressive hearing loss, resulting in diagnostic delay, making it a clinical rarity, and hence it is selected as a case report. Keywords: Otosclerosis, Deafness, Quality Of Life, Tympanic Membrane